The impact of Orange-Fleshed Sweetpotato in Mozambique: A research proposal - Brouwer, R.; Munda, E.; Francisco, E.; Naico, A.; Mulwa, C.K.; Okello, J.J.; Gatto; M.; Hareau, G. (2024)
The present document is a research proposal to assess the impact CIP work in Mozambique with emphasis on sweetpotato, and more particular on orange-fleshed cultivars (OFSP), which are rich in beta-carotene, a plant-based source of the essential micro-nutrient vitamin A. The study proposes to address three large sets of research questions: a) to what extent OFSP cultivars have been integrated in the local farming systems, and what are the factors that explain adoption, dis-adoption and rejection, b) the extent to which changes that can be observed in poverty, livelihoods, employment, and resilience can be associated with the adoption of OFSP cultivars, and c) what are the causal pathways that explain the connection between OFSP adoption and the livelihood changes that can be observed.